A Cross-sectional Study on the Prevalence of Depression in Arunachal Pradesh - Siram, Tani; Perme, Obang; Komut, Ojing (Nepal Journal of Neuroscience, 2022)
Introduction: Depression is a commonly occurring mental disorder. Depression affects patients across all age groups, socioeconomic statuses, and genders. To determine the prevalence of depression in patient attending OPD clinic in Pasighat, Arunachal Pradesh using the Patient Health Questionnaire (PHQ-9). Methods: This is a cross-sectional study of fifty randomly selected patients in the OPD Clinic of Bakin Pertin General Hospital in Pasighat, Arunachal Pradesh, between the period 2017 and 2018. Eligible patients ranged in age from 13 to 70 years old and represented both rural and urban areas. Results: The study found that twenty-one out of fifty patients, i.e., 42% of patients, suffered from minimal to mild depressive symptoms. Conclusion: The study showed a high prevalence of depression in East Siang district (Pasighat), Arunachal Pradesh, and parts of adjoining districts of Pasighat. A combination of approaches could help in providing the best possible care for patients with mental disorders and assist them in living fulfilling lives.